DIFFERENTIAL EXPRESSION OF QUANTITATIVE TRAITS IN MULTIVOLTINE RACES AND BIVOLTINE BREEDS OF SILKWORM BOMBYX MORI BOMBYX MORI L. L. - R. ANANTHA; G. SUBRAMANYA (The Bioscan, 2010)
Six multivoltine races and four bivoltine breeds were reared in three replicates each in three different seasons of a year. Thirteen quantitative traits of economic importance were analyzed through analysis of variance to understand the interaction between each races/ breeds, seasons and quantitative traits. The performance of the multivoltine races for the viability traits such as yield by number and pupation rate was highly significant where as among the bivoltine breeds, NB4 D2 and CSR2 revealed significant higher values for cocoon weight, shell weight, shell percentage and filament length compared to multivoltine races. All the races irrespective of the voltinism exhibited higher values for productivity traits in the monsoon period of the year. The expression of thirteen quantitative traits of both multivoltine and bivoltine races are discussed in regard to the importance of favourable environment for productivity traits.